The Current State of the Formation of Emotional Literacy of Older Preschool Children with Logopathology - Bielova, Olena (Educological discourse, 2023)
The purpose of this study is to identify the current state of emotional literacy, which affects the speech readiness to study at school of older preschool children with logopathology. The main priority of older preschoolers is that they are already able to manage their emotions and feelings, which acquire stability and validity. During training, moral, aesthetic, motivational, cognitive feelings are built on their basis. Emotional readiness determines in children an adequate reaction to life situations, understanding of actions and consequences of emotional states (emotional prediction); awareness of one's experiences, the ability to explain one's condition (feelings become arbitrary, controlled), which is extremely important for a future student. This especially applies to children with speech pathology. The results of the experimental study give a clear idea that there are significant differences between the groups of children with logopathology and those with normotypical psychophysical development regarding the formation of the emotional component of the psychological component of speech readiness for school: insufficiently formed knowledge about schematic types of emotions, which reveals a low level of awareness and ideas about types of emotions and their properties; insufficiently developed ability to analyze the facial expressions of the close environment; not understanding what kind of emotion a person can feel in different life situations. Their knowledge is limited to a small number of emotions, so during mood swings it is difficult for them to explain their emotional state or identify it in others; during communication, negative emotions are inherent (stubbornness, behavioral negativism, anxiety, fear of something new, in particular, speech). The obtained research materials and statistical evidence allow us to conclude that the majority of older preschool children with logopathology have an insufficiently formed emotional regulation; more often than children with normotypical development, they experience negative emotions during communication both with peers and with adults. The research materials indicate the unformed readiness of this category of children to interact in the conditions of schooling.